ANTIOXIDANT ACTIVITY TEST OF METHANOL EXTRACT ON DRAGON FRUIT SKIN (Hylocereus polyrhizus), BENGKOANG (Pachyrhizus erosus) AND GUAVA SEEDS (Syzygium malaccense L) DPPH METHOD (1,1-Dyphenyl-2-Pycrylhydrazyl) - Rosa Devitria; Nadila Pratiwi Utami (LPPM Universitas Abdurrab, 2025)
Free radicals are components that lack one electron, so they are very reactive toward other components to complement their electron deficiency. Free radicals have become a frightening component for many people because of the problems they cause, such as premature aging and various degenerative diseases. However, free radicals and the reactions they form can be inhibited by antioxidant compounds. According to WHO (World Health Organization), in 2011 showed that several degenerative diseases such as atherosclerosis, stroke, diabetes mellitus, and others are included in the top ten causes of human death worldwide. To prevent degenerative diseases, antioxidants are needed, which can neutralize free radicals. The function of antioxidants is to help the defense system in the body when disease-generating elements enter and attack the body. Dragon fruit skin, jicama, and guava seeds contain flavonoids to prevent skin damage due to free radicals, and phenolic substances are effective in inhibiting the process of melanin formation. Aims to determine the antioxidant activity test of methanol extract made from dragon fruit skin, Sengkang and guava seeds using the DPPH method. This research is laboratory experimental research. This research is laboratory experimental research. Dragon fruit skin, Sengkang and guava seeds are dried and mashed and then macerated with a methanol solution. Furthermore, testing of antioxidant activity was carried out using the DPPH method (1,1-Dyphenyl-2-Pycrylhydrazyl) and using a microplate reader at a wavelength of 520 nm. The results of the antioxidant activity test of the methanol extract on the antioxidant test of the dragon fruit peel extract sample obtained an IC50₋ value of 286.816 ppm which was included in the weak group; the antioxidant test of the Sengkang extract sample obtained an IC50- value of 31.218 ppm which was included in the weak group. Very strong, the antioxidant test of the guava seed extract sample obtained an IC50- value of 15.958 ppm which is included in the very strong group.